OPTYMALIZACYJNY MODEL FUNKCJONOWANIA ODESŁAŃ POZAPRAWNYCH W PRAKTYCE SĄDOWEJ - Leszczyński, Leszek (Wydział Prawa i Administracji UAM, 2000)
The aim of the work is an attempt to draw up an optimalising model which - taking into consideration all systemic and legal changes of the last decade in Poland - should stress the most desired properties of having recourse to renvoy clauses in judicial practice - from the point of view of building up democratic and market systems. Such a model should additionally meet the requirement of lawful character of the State as formulated in the Constitution of the Republic of Poland.
OPTIMALIZING MODEL OF FUNCTIONING OF EXTRA-LEGAL RENVOYS IN JUDICIAL PRACTICE